The contribution of childhood circumstances, current circumstances and health behaviour to educational health differences in early adulthood - Härkänen Tommi; Rahkonen Ossi; Martelin Tuija; Kestilä Laura; Koskinen Seppo (BMC, 2009)
Abstract Background The life course approach emphasises the contribution of circumstances in childhood and youth to adult health inequalities. However, there is still a lot to know of the contribution of living conditions in childhood and youth to adult health inequalities and how later environmental and behavioural factors are connected with the effects of earlier circumstances. This study aims to assess a) how much childhood circumstances, current circumstances and health behaviour contribute to educational health differences and b) to which extent the effect of childhood circumstances on educational health differences is shared with the effects of later living conditions and health behaviour in young adults. Methods The data derived from the Health 2000 Survey represent the Finnish young adults aged 18-29 in 2000. The analyses were carried out on 68% (n = 1282) of the sample (N = 1894). The cross-sectional data based on interviews and questionnaires include retrospective information on childhood circumstances. The outcome measure was poor self-rated health. Results Poor self-rated health was much more common among subjects with primary education only than among those in the highest educational category (OR 4.69, 95% CI 2.63 to 8.62). Childhood circumstances contributed substantially (24%) to the health differences between these educational groups. Nearly two thirds (63%) of this contribution was shared with behavioural factors adopted by early adulthood, and 17% with current circumstances. Health behaviours, smoking especially, were strongly contributed to educational health differences. Conclusion To develop means for avoiding undesirable trajectories along which poor health and health differences develop, it is necessary to understand the pathways to health inequalities and know how to improve the living conditions of families with children.